Biomimetic multidirectional scaffolds for zonal osteochondral tissue engineering via a lyophilization bonding approach. Issue 4 (1st December 2017) - Clearfield, Drew; Nguyen, Andrew; Wei, Mei
Abstract: The zonal organization of osteochondral tissue underlies its long term function. Despite this, tissue engineering strategies targeted for osteochondral repair commonly rely on the use of isotropic biomaterials for tissue reconstruction. There exists a need for a new class of highly biomimetic, anisotropic scaffolds that may allow for the engineering of new tissue with zonal properties. To address this need, we report the facile production of monolithic multidirectional collagen‐based scaffolds that recapitulate the zonal structure and composition of osteochondral tissue. First, superficial and osseous zone‐mimicking scaffolds were fabricated by unidirectional freeze casting collagen‐hyaluronic acid and collagen‐hydroxyapatite‐containing suspensions, respectively. Following their production, a lyophilization bonding process was used to conjoin these scaffolds with a distinct collagen‐hyaluronic acid suspension mimicking the composition of the transition zone. Resulting matrices contained a thin, highly aligned superficial zone that interfaced with a cellular transition zone and vertically oriented calcified cartilage and osseous zones. Confocal microscopy confirmed a zone‐specific localization of hyaluronic acid, reflecting the depth‐dependent increase of glycosaminoglycans in the native tissue. Poorly crystalline, carbonated hydroxyapatite was localized to the calcified cartilage and osseous zones and bordered the transition zone. Compressive testing of hydrated scaffold zones confirmed an increase of stiffness with scaffold depth, where compressive moduli of chondral and osseous zones fell within or near ranges conducive for chondrogenesis or osteogenesis of mesenchymal stem cells. With the combination of these biomimetic architectural and compositional cues, these multidirectional scaffolds hold great promise for the engineering of zonal osteochondral tissue. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 948–958, 2018.